1998
DOI: 10.1007/s004290050189
|View full text |Cite
|
Sign up to set email alerts
|

Light and electron microscopic studies of pituitary adenylate cyclase-activating peptide (PACAP) - immunoreactive neurons in the enteric nervous system of rat small and large intestine

Abstract: Pituitary adenylate cyclase-activating peptide (PACAP)-immunoreactive (IR) neurons in the myenteric and submucosal plexus of the rat small and large intestine were examined by immunostaining with purified polyclonal antiserum against PACAP (1-15), using both light and electron microscopy. Many PACAP-IR neuronal cell bodies and fibers were found in the myenteric and submucosal plexus. Many of the PACAP-IR fibers originated from the cell bodies of the myenteric and submucosal ganglia. The ganglia were also inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…In these lower vertebrates, VIP/PACAP-IR nerve fibers were most abundant in the myenteric ganglia and in circular and longitudinal muscle layers. In X. laevis (Olsson 2002) and Axolotl myenteric plexus, VIP-/PACAP-IR fibers were often adjacent to non-immunoreactive neurons as has also been shown electron microscopically for PACAP-IR fibers in rat intestine (Nagahama et al 1998). These fibers may stem from extrinsic neurons and regulate the action of myenteric neurons, but it is also conceivable that they originate from interneurons, as has been suggested .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In these lower vertebrates, VIP/PACAP-IR nerve fibers were most abundant in the myenteric ganglia and in circular and longitudinal muscle layers. In X. laevis (Olsson 2002) and Axolotl myenteric plexus, VIP-/PACAP-IR fibers were often adjacent to non-immunoreactive neurons as has also been shown electron microscopically for PACAP-IR fibers in rat intestine (Nagahama et al 1998). These fibers may stem from extrinsic neurons and regulate the action of myenteric neurons, but it is also conceivable that they originate from interneurons, as has been suggested .…”
Section: Discussionmentioning
confidence: 82%
“…PACAP, too has been localised immunohistochemically in representatives of different vertebrate classes. PACAP-IR nerve fibers have been described in mammalians, such as the rat, the mouse, the hamster, the guinea pig, the ferret, the cat, the pig, the sheep and in humans (Sundler et al 1992;Köves et al 1993;Portbury et al 1995;Hannibal et al 1998;Nagahama et al 1998;Kirchgessner and Liu 2001), in birds, i.e. chickens (Sundler et al 1992;Salvi et al 2000), in anurans (Xenopus laevis) (Olsson 2002), and in bony fish, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The mixture was neutralized with 1 N HCl (300 μL) and incubated for 20 min. After centrifugation at 12,000 × g for 20 min at 4°C, PACAP(1-15)-IR in the pellets was measured by the PACAP(1-15) RIA system (18).…”
Section: Cellular Uptake Of Pthrp(87-107)mentioning
confidence: 99%
“…In the gastrointestinal tract, PACAP immunoreactivity is widely distributed (Uddman et al 1991;Sundler et al 1992; Köves et al 1993;Ny et al 1995;Olsson and Holmgren 1994;Nagahama et al 1998) and PACAP mRNA has been found to be expressed in the intestine of some mammalian and non-mammalian species (Arimura 1992;McRory et al 1995;Hannibal et al 1998;Fradinger and Sherwood 2000;Matsuda et al 2000). Gastrointestinal PACAP has both an intrinsic and extrinsic origin (Portbury et al 1995;Hannibal et al 1998) and seems to be involved in the modulation of gastrointestinal motility, secretion and proliferation Lindström et al 1997; for a review, see Läuffer et al 1999).…”
Section: Introductionmentioning
confidence: 99%